2003
DOI: 10.1038/sj.leu.2402673
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of high-dose methylprednisolone in comparison with conventional-dose prednisolone during remission induction therapy in childhood acute lymphoblastic leukemia for long-term follow-up

Abstract: Eight-year event-free survival (EFS) was evaluated in 205 patients with acute lymphoblastic leukemia (ALL), to consider the efficacy of high-dose methylprednisolone (HDMP) given during remission induction chemotherapy between 1 and 29 days. The St Jude Total XI Study protocol was used after some minor modifications in this trial. Patients were randomized into two groups. Group A (n = 108) received conventional dose (60 mg/m 2 /day orally) prednisolone and group B (n = 97) received HDMP (Prednol-L, 900-600 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…Diagnosis of ALL and risk criteria of relapse were made according to standard hematological findings [10][11][12]. Chemotherapy had been given according to the modified St. Jude Total XI and Total XIII protocols in 74 and 42 patients, respectively [10,11] (Table I).…”
Section: Methodsmentioning
confidence: 99%
“…Diagnosis of ALL and risk criteria of relapse were made according to standard hematological findings [10][11][12]. Chemotherapy had been given according to the modified St. Jude Total XI and Total XIII protocols in 74 and 42 patients, respectively [10,11] (Table I).…”
Section: Methodsmentioning
confidence: 99%
“…In this cross-sectional study, we evaluated 108 children (68 boys and 40 girls) who were diagnosed with ALL at Hacettepe University Hospital between January 1995 and December 2000 and treated according to the current ALL protocols of Hacettepe University Childhood Leukemia Study Group, which was the St. Jude ALL Total Therapy Study XI protocol with minor modification [17,18]. The patients were divided into two groups.…”
Section: Patientsmentioning
confidence: 99%
“…The patients were divided into two groups. In order to have matched groups with respect to the time intervals after cessation of chemotherapy, 59 patients [36 boys and 23 girls; median age 11.7 years (range [6][7][8][9][10][11][12][13][14][15][16][17][18][19]] out of 108 were enrolled in the study. The only difference of the two protocols was the dose of corticosteroid during remission-induction chemotherapy: group 1 (n ¼ 30) received ''conventional-dose prednisolone therapy (CDP; prednisolone, 2 mg/kg/day, orally)'' and group 2 (n ¼ 29) received ''high-dose methylprednisone therapy (HDMP; Prednol-L, 900-600 mg/m 2 , orally)'' ( Table I).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that the 8-year EFS was significantly higher [14]. To verify whether HDMP was more effective on blast reduction rate than conventional dose steroid therapy, we analyzed the outcome of 194 ALL patients for initial response and presenting features.…”
Section: Introductionmentioning
confidence: 98%